School Functioning in Adolescents With Chronic Fatigue Syndrome - Knight, Sarah Jenette; Politis, Jennifer; Garnham, Christine; Scheinberg, Adam; Tollit, Michelle Anne (Frontiers in Pediatrics, 2018)
Background: It is well known that adolescents with chronic fatigue syndrome (CFS) experience greater school absenteeism compared to healthy adolescents. Less is known about other important aspects of school functioning including school participation, school connectedness and academic performance in students with CFS. The aim of this study was to compare school functioning as a multifaceted construct in adolescents with CFS to healthy adolescent peers. We also explored whether illness factors were associated with school functioning in adolescents with CFS. Methods: Thirty-nine participants with CFS and 28 healthy controls (aged 13-17 years) completed a range of subjective and objective measures of school functioning, as well as measures of fatigue and emotional symptoms. Results: Adolescents with CFS demonstrated significantly higher rates of school absence, as well as poorer school-related quality of life, reduced school participation, poorer connectedness with school, and reduced academic performance. Fatigue severity and emotional symptoms were significantly associated with most aspects of school function. Conclusions: Adolescents with CFS are at increased risk for poor school functioning across a range of indicators which extend beyond school absenteeism.